B6.Rag1 Knockout Mice Generated at the Jackson Laboratory in 2009 Show a Robust Wild-Type Hypertensive Phenotype in Response to Ang II (Angiotensin II). Issue 4 (April 2020) - Seniuk, Anika; Thiele, Jonas L.; Stubbe, Andra; Oser, Philipp; Rosendahl, Alva; Bode, Marlies; Meyer-Schwesinger, Catherine; Wenzel, Ulrich O.; Ehmke, Heimo
Abstract : A key finding supporting a causal role of the immune system in the pathogenesis of hypertension is the observation that RAG1 knockout mice on a C57Bl/6J background (B6.Rag1 −/ − ), which lack functional B and T cells, develop a much milder hypertensive response to Ang II (angiotensin II) than control C57Bl/6J mice. Here, we report that we never observed any Ang II resistance of B6.Rag1 −/− mice purchased directly from the Jackson Laboratory as early as 2009. B6.Rag1 −/− mice displayed nearly identical blood pressure increases monitored via radiotelemetry and hypertensive end-organ damage in response to different doses of Ang II and different levels of salt intake (0.02%, 0.3%, and 3% NaCl diet). Similarly, restoration of T-cell immunity by adoptive cell transfer did not affect the blood pressure response to Ang II in B6.Rag1 −/− mice. Full development of the hypertension-resistant phenotype in B6.Rag1 −/− mice appears to depend on the action of yet unidentified nongenetic modifiers in addition to the absence of functional T cells. Abstract : Supplemental Digital Content is available in the text.